Plain radiography is effective for the detection of calcinosis cutis occurring in association with autoimmune connective tissue disease. (1st May 2014) - Shahi, V.; Wetter, D.A.; Howe, B.M.; Ringler, M.D.; Davis, M.D.P.
Summary: Background: Studies on the radiological findings of calcinosis cutis in patients with autoimmune connective tissue disease (ACTD) are limited. Objectives: To describe imaging findings and radiological patterns of calcinosis cutis occurring with ACTD. Methods: We retrospectively reviewed the cases of 37 patients with imaging studies assessing for calcinosis cutis associated with ACTD at our institution between 1996 and 2009. A formal blinded review of available images (i.e. radiographs, computed tomography scans) for all 37 patients was performed by radiologists. Results: Of 37 patients, 30 (81%) were female. The mean age at diagnosis of calcinosis cutis was 43·4 years. Patients had the following ACTDs: dermatomyositis ( n = 17) with classic ( n = 9), juvenile ( n = 7) and amyopathic ( n = 1) subtypes; systemic sclerosis with limited cutaneous scleroderma ( n = 8); undifferentiated connective tissue disease ( n = 4); mixed connective tissue disease ( n = 3); systemic lupus erythematosus ( n = 2); lupus panniculitis ( n = 1); overlap connective tissue disease ( n = 1); and polymyositis ( n = 1). Plain radiographs detected calcinosis in all 37 patients; a nodular pattern of calcification was most commonly observed (31/37; 84%). Two or more morphological patterns of calcification were present in 19 patients (51%). In general, individual patterns were not specific to a particular ACTD subtype. Conclusions: Radiography detected calcinosis in all patients and is recommended for initial imaging of calcinosis. Multiple morphological patterns of calcification were observed across ACTD subtypes. Further studies should correlate radiological studies with treatment of calcinosis and underlying ACTD.